2013
DOI: 10.1530/rep-13-0203
|View full text |Cite
|
Sign up to set email alerts
|

Application of a novel cell-permeable peptide-driven protein delivery in mouse blastocysts

Abstract: Cell-permeable peptides (CPPs) mediate the delivery of macromolecules into cells. However, whether CPPs are usable in mammalian oocytes and embryos for the modulation of protein expression has not been widely investigated. We have previously designed a novel 12-mer CPP from the conserved region of the human papillomavirus L1 capsid protein.In this study, we tested whether this peptide, LDP12, effectively delivers a protein cargo to mouse oocytes and preimplantation embryos. We prepared a LDP12-EGFP fusion prot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Previous studies have demonstrated that hydrophilic arginine-rich cell-penetrating peptides have optimal internalization capability for small molecules in mammalian cells (Mitchell et al, 2000;Mueller et al, 2008;Tünnemann et al, 2008). Presently, there is a limited amount of literature available on the utilization of CPPs in oocytes (Kwon et al, 2009;Kwon et al, 2013;Yang et al, 2014;Jeon et al, 2019;Zhu et al, 2021), and none of these studies extensively examine the internalization of CPPs into mouse oocytes. First, we evaluated the ability of CPPs to cross both the zona pellucida and plasma membrane of immature (GV) and mature (MII) mouse oocytes within a 1 h incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hydrophilic arginine-rich cell-penetrating peptides have optimal internalization capability for small molecules in mammalian cells (Mitchell et al, 2000;Mueller et al, 2008;Tünnemann et al, 2008). Presently, there is a limited amount of literature available on the utilization of CPPs in oocytes (Kwon et al, 2009;Kwon et al, 2013;Yang et al, 2014;Jeon et al, 2019;Zhu et al, 2021), and none of these studies extensively examine the internalization of CPPs into mouse oocytes. First, we evaluated the ability of CPPs to cross both the zona pellucida and plasma membrane of immature (GV) and mature (MII) mouse oocytes within a 1 h incubation period.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have demonstrated that hydrophilic arginine-rich cell-penetrating peptides have optimal internalization capability for small molecules in mammalian cells ( Mitchell et al, 2000 ; Mueller et al, 2008 ; Tünnemann et al, 2008 ). Presently, there is a limited amount of literature available on the utilization of CPPs in oocytes ( Kwon et al, 2009 ; Kwon et al, 2013 ; Yang et al, 2014 ; Jeon et al, 2019 ; Zhu et al, 2021 ), and none of these studies extensively examine the internalization of CPPs into mouse oocytes.…”
Section: Discussionmentioning
confidence: 99%
“…The same group also tested a 12-mer CPP from the conserved region of the human papillomavirus L1 capsid protein, LDP12. Nevertheless, CPP was not internalized in mature oocytes (with or without ZP) and was not assayed in immature oocytes (S. Kwon et al, 2013 ). In this work, we have demonstrated that CPP internalization observation depends on the mounting method.…”
Section: Discussionmentioning
confidence: 99%
“…It was recently reported that induced pluripotent cells (iPSCs) could be generated by introducing transcription factors fused with a cell-penetrating peptide (CPP) 21 , 22 . Lim and colleagues also identified a new form of CPP, obtained from human papillomavirus L1 capsid protein (LDP12), and confirmed its ability to deliver a fusion protein of enhanced green fluorescence protein and MAP1LC3 (EGFP-LC3) into mouse blastocysts 23 . In our previously reports, the cell number of inner cell mass (ICM) and expression of the Oct4 gene were positively regulated in fresh and cryopreserved embryos after treatment with CPP-conjugated estrogen-related receptor β (CPP-ESRRB) during in vitro cultivation 24 , 25 .…”
Section: Introductionmentioning
confidence: 92%